Specific binding of human corticosteroid-binding globulin to cell membranes. - Hryb, D J (1986)
Specific binding sites for corticosteroid-binding globulin were detected on membranes prepared from human prostates. The binding sites are typical of membrane receptors: they are saturable and specific and have high affinity. There was little specific binding at 4 degrees C and 23 degrees C. Maximal specific binding was obtained at 37 degrees C. Scatchard analysis revealed the presence of a single set of binding sites with an apparent dissociation constant of 8.7 X 10(-7) M and a binding capacity of 22 pmol/mg of membrane protein. The sites were specific for corticosteroid-binding globulin; binding was not inhibited by human testosterone/estradiol-binding globulin, by albumin, or by transferrin. The density of specific binding sites in membranes obtained from several organs from the rhesus monkey is consistent with the hypothesis that corticosteroid-binding globulin is involved in the transport of steroid hormones into target tissues.